Karakterisasi Dan Seleksi Galur F3 Hasil Persilangan Cabai Katokkon (Capsicum Annuum L.) Dengan Cabai Rawit (Capsicum Frutescens L.) - Berlian Zetikarya Haryati (AgroSainT, 2020)
Study on F3 Line Selection and Characterization At Kakondongan, Tallunglipu District, North Toraja Regency, Cayenne pepper (Capsicum frutescens L.) and Katokkon chili (Capsicum annuum L.) were crossed. The goal of this study is to choose the F3 lines produced by crossing Katokkon and Rawit chilies in order to extract novel features from their parents. Weighted (WINDEX) and unweighted (UNWINDEX) selection methods were used to construct the research. The plants are made up of 21 lines, and there are five potential plants on each line, making a total of 105 chili plants. The findings revealed that G3Y2-2, G7Y7-5, G7Y9-2, G10Y9-4, G7Y9-1, G9Y7-4, G4Y2-2, G7Y7-1, G5Y10-3, and G3Y2-4 were the lines chosen through weighted selection.G3Y1-2, G3Y2-2, G7Y7-5, G7Y7-1, G9Y7-4, G7Y9-2, G7Y9-1, G10Y9-4, G3Y2-4, and G9Y7-5 were the lines that were not chosen through unweighted selection.